Do physical qualities influence the attainment of professional status within elite 16-19 year old rugby league players? - Till, K.; Jones, B.; Geeson-Brown, T. (Journal of Science and Medicine in Sport, 2016)
Objectives: The current study retrospectively compared the physical qualities of elite academy rugby league players (aged 16-19 years) by career attainment level (i.e., academy or professional). Design: Retrospective cross-sectional and longitudinal design. Methods: Eighty-one academy rugby league players were assessed for physical qualities (height, body mass, skinfolds, speed, momentum, vertical jump, Yo-Yo Level 1 and 1-RM squat, bench press and prone row) at the Under 17-19 age categories between 2007 and 2012. Player's career attainment level was determined in 2014. Longitudinal changes in physical qualities between Under 17 and 19s were compared by career attainment level. Results: Professional players demonstrated moderate significant advantages for height (d = 0.98) and 1-RM squat (d = 0.66) at the Under 17s, 1-RM bench press (d = 0.76) at the Under 18s and 1-RM prone row (d = 0.73) at the Under 19s age categories when compared to academy players. When assessed longitudinally (Under 17s-19s), professional players significantly outperformed academy players for 1-RM squat (2 = 0.20). Professional players also demonstrated greater increases in body mass (8.2 vs. 2.9 kg) and 10 m momentum (47 vs. 17 kg s-1) than academy players between the Under 17s and 19s. Conclusions: Advanced physical qualities, particularly height and absolute strength, within 16-19 year old players may contribute to attaining professional status in rugby league. Further, the development of body mass and momentum for players within an academy is an important consideration in the progress towards professional rugby league. Therefore, practitioners should aim to identify and develop the physical qualities, especially size and strength, within academy rugby league players.